CAREGIVERS IN THE SYSTEM OF HIGHER EDUCATION THAT CREATIVE POTENTIAL DEVELOPMENT OPTIONS (Academia Science Repository, 2023)
In this article referred to potential caregivers in the development of creative thinking. Development of creative potential of the main caregivers in the formation of the quality of creative work to see a clear priority on the basis of the principle of goal-oriented thinking and find innovative approach highlighting the effectiveness of the decision was to conduct offbeat activity. The creative potential of caregivers improvementat giving many suggestions to organize sessions than mentioned.